2018
DOI: 10.1111/anu.12669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fungal fermentation on apparent digestibility coefficient for dry matter, crude protein and amino acids of various plant protein sources in Penaeus vannamei

Abstract: Four commercial solvent‐extracted oilseed meals/cakes, viz. soybean meal (SBM), groundnut oil cake (GNC), rapeseed meal (RSM) and sunflower oil cake (SFC), were fermented with fungus Aspergillus niger, and its effect on apparent digestibility coefficient (ADC) was studied in Penaeus vannamei. Reference diet and eight experimental diets containing 700 g/kg reference diet and 300 g/kg test ingredient with 5 g/kg chromic oxide were formulated. Each diet was randomly allotted to three tanks containing ten shrimps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…The APD of selected fermented plant proteins found to be in the range of 84.97% to 93.71% in P. monodon and 86.54% to 95.12% in P. indicus. The values found in our study were higher than those reported earlier for untreated plant protein sources in penaeid shrimps (Carvalho et al, ; Chen et al, ; Jannathulla, Dayal, Vasanthakumar et al, ). This indicates that the fermented plant proteins could effectively be used by the penaeid shrimps.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The APD of selected fermented plant proteins found to be in the range of 84.97% to 93.71% in P. monodon and 86.54% to 95.12% in P. indicus. The values found in our study were higher than those reported earlier for untreated plant protein sources in penaeid shrimps (Carvalho et al, ; Chen et al, ; Jannathulla, Dayal, Vasanthakumar et al, ). This indicates that the fermented plant proteins could effectively be used by the penaeid shrimps.…”
Section: Discussionmentioning
confidence: 91%
“…The highest AAD for FSBM was recorded for lysine (96.93%) in P. monodon and arginine (97.62%) in P. indicus. However, in our previous study (Jannathulla, Dayal, Vasanthakumar et al, ) the highest digestibility to methionine (98.75%) was observed in P. vannamei. Nevertheless, the values reported earlier for essential amino acids varied slightly (Carvalho et al, ; Chen et al, ; Jannathulla, Dayal, Vasanthakumar et al, ).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations